Determination of the activation energy of silicone rubbers using different kinetic analysis methods - Ou Huibin; Sahli Mohamed; Barriere Thierry; Gelin Jean-Claude (MATEC Web of Conferences, 2016)
The solidification of silicone rubbers is a crosslinking reaction called vulcanization. It follows that the physical and mechanical properties of silicone rubbers increase significantly due to the growth of molecular weight and were affected strongly by the vulcanization process, such as the temperatures and times for curing. In this study, the kinetics of the crosslinking reaction of silicone rubbers was investigated by two current techniques: differential scanning calorimeter (DSC) and oscillating disk rheometry (ODR). From the kinetic experimental data, different kinetic analysis methods were used to determine the activation energy of silicone rubbers, such as the Kissinger, the Ozawa, the Friedman, the Flynn-Wall-Ozawa, the Kissinger-Akahira-Sunose and the integral methods. The results show the influence of the chemical composition of silicone rubbers, the current technique used and the applied kinetic analysis methods on the activation energy and the evolution of activation energy during the crosslinking reaction.